Child Health in the Peruvian Amazon: Prevalence and Factors Associated with Referred Morbidity and Health Care Access in the City of Iñapari. (10th November 2015) - Guimarães, Maria Gabriela Silva; Braña, Athos Muniz; Oliart-Guzmán, Humberto; Branco, Fernando Luiz Cunha Castelo; Delfino, Breno Matos; Pereira, Thasciany Moraes; Mantovani, Saulo Augusto Silva; Martins, Antonio Camargo; Santos, Ana Paula; Filgueira-Júnior, José Alcântara; Ramalho, Alanderson Alves; Guimarães, Andreia da Silva; et al.
Abstract : Introduction . Children under 5 years of age are more susceptible to developing morbidities such as diarrhea, respiratory infections, anemia, and malnutrition. The objective of the study is to evaluate the prevalence of reported morbidities in this age group in the city of Iñapari (Peru) and the access to health services in this municipality. Methods . Data collection using interviews that assessed socioeconomic and demographic conditions, child morbidity, and access to health services was performed in 2011. Statistical analysis was performed using SPSS 13.0. Results . Regarding morbidities that occurred during lifetime, 39.8% reported previous anemia and intestinal parasite infection. About 53.7% of the children reported any type of morbidities in the last 15 days before interview, being most frequent respiratory symptoms (38.9%), diarrhea (23, 4%), and fever (23, 1%). Only 63.1% of those reporting recent morbidities sought health care. These morbidities were associated with precarious sanitation and lack of infrastructure, the presence of other comorbidities, and poor access to health services. Conclusion . The main referred morbidities in Amazonian Peruvian children were diarrhea, respiratory symptoms, anemia, and vomiting. Incentives and improvements in the health and sanitation conditions would be important measures to improve the quality of life of the Amazonian child population.